2020
DOI: 10.1109/access.2020.3017015
|View full text |Cite
|
Sign up to set email alerts
|

Transient Modeling Method for Faulty DC Microgrid Considering Control Effect of DC/AC and DC/DC Converters

Abstract: The accurate transient modeling of faulty DC microgrids is the basis of fault detection, fault location and fault isolation. AC/DC and DC/DC converters keeps their normal control strategies until the fault is detected. However, in existing researches, the influence of the control effect of converters is normally being ignored in the transient characteristics of DC microgrids. This omission reduces the accuracy of the faulty transient model. Thus, this paper proposes a transient modeling method for faulty DC mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In future work, the hardware-in-the-loop will be conducted to perform real-time simulation of the power system [47][48][49]. The platform used to execute the proposed framework is OPAL-RT OP5600 equipped in UNSW RTS lab.…”
Section: Discussionmentioning
confidence: 99%
“…In future work, the hardware-in-the-loop will be conducted to perform real-time simulation of the power system [47][48][49]. The platform used to execute the proposed framework is OPAL-RT OP5600 equipped in UNSW RTS lab.…”
Section: Discussionmentioning
confidence: 99%
“…Pachanapan [48] presented a dynamic model of the grid-tied inverters used in battery and PV systems. Kong and Nian [49] proposed a transient modelling method for DC microgrids that considered the control effects of different DC/AC and DC/DC converters; their results showed that the proposed method can not only improve the accuracy of transient analysis of the DC microgrids, but can also enhance the calculation efficiency. To mitigate the effects of multiple uncertainties and realize economical operation of an AC/DC hybrid microgrid, a temporally coordinated energy management strategy was proposed for the AC/DC hybrid microgrid which considered the dynamic conversion efficiency of the bidirectional AC/DC converter in [50].…”
Section: State-of-the-artmentioning
confidence: 99%
“…Figure 14 shows the ES block diagram to implement the model of Equation (29). The scheme presented in Figure 14 shows the PI controller of the PLL of Figure 7; however, similar diagrams were used for the inner loop and outer loop controllers of the control structure.…”
Section: Controllermentioning
confidence: 99%
“…For the design and implementation of HILPs to emulate DC µGs, various DBs have been used. In [29], the Typhoon 602+ platform was used to emulate the behavior of a DC µG with an IT of 1 µs, while for the TMS32028335DSPC, Spartan 6XC6SLX16FPGA DBs were used to control the different converters, which operate with a modulation frequency of 10 kHz. These implementations were carried out to analyze the effect of the drivers on the transitions of the DC µG converters.…”
Section: Introductionmentioning
confidence: 99%